2005
DOI: 10.1111/j.1464-410x.2005.05400.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual, psychological and dyadic qualities of the prostate cancer ‘couple’

Abstract: Information from this study could be useful in constructing interventions that allow the physician and the prostate cancer 'couple' to reflect on issues of sexual function and psychological distress that might once have been considered taboo. The results characterize the disparities between patients with prostate cancer and their partners on self-reported questionnaires, and underscore how important it is to hear the voice of the 'couple'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 27 publications
4
92
1
6
Order By: Relevance
“…64 In general, partners of PCa sufferers describe even more distress than the patients. 65 It has been observed that partners often want to talk about the ADT-associated changes, while the patient wants to minimize the issues.…”
Section: Relationship Changesmentioning
confidence: 99%
“…64 In general, partners of PCa sufferers describe even more distress than the patients. 65 It has been observed that partners often want to talk about the ADT-associated changes, while the patient wants to minimize the issues.…”
Section: Relationship Changesmentioning
confidence: 99%
“…Research suggests that not only is the patient affected by these events but also the partner (4,5). When men are in a stable relationship, the couple's perspective becomes an important issue and necessitates a refocusing of outcomes directed to the prostate cancer "couple" (5). Although sexual dysfunction has been shown to be related to psychological impairment in males (2), this aspect has not been yet addressed from a couple perspective.…”
Section: Introductionmentioning
confidence: 98%
“…Prostate cancer surgery will result in variable degrees of impaired urinary control and sexual dysfunction. Research suggests that not only is the patient affected by these events but also the partner (4,5). When men are in a stable relationship, the couple's perspective becomes an important issue and necessitates a refocusing of outcomes directed to the prostate cancer "couple" (5).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Studies have found that psychological distress is equivalent regardless of the fact whether the person is the patient or partner. 10 Clearly, once cancer is discovered in either partner, both experience an increased level of anxiety compared with healthy couples.…”
Section: Introductionmentioning
confidence: 99%